PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR KAWASAKI ( Pada PT. Sinargemala Sakti Semarang ) - Pandu Kurniawan, 08.05.51.0127; Nawatmi, Sri (Students Journal of Economic and Management, 2012)
All motorcycle manufacturers competing to create new innovations, models and designs continue to be tested and developed according to consumer tastes. Conducted a massive promotion in various media, both print and electronic. This indicates that the motorcycle market demand is very high. The high demand is not only because of needed factors, but also heavily influenced by other factors, such as income level, product attributes, price, brand, method of payment, the resale price, reference group and location. This research used quality of product, price and promotion as an independent variable and the purchase decision as the dependent variable. Sampling method in this study is purposive sampling techniques and the amount of samples are 100 respondents.The research show that the assumption of classical regression model is free from multicollinearity, autocorrelation and heteroscedasticity. As for the research of determination coefficient values obtained that the purchase decision can be explained by the three independent variables. The test research f obtained that the variable quality of product, price and promotion of a positive influence on purchase decisions. Based on regression analysis obtained the variable quality of product and promotion have a positive influence for purchase decision, as for price variable have negative influence. For the hypothesis test used the t test, based on hypothesis testing variables quality product, price and promotion can be accepted.Key words: quality of product, price, promotion and purchasing decisions.